Controlling spontaneous emission from perovskite nanocrystals with metal–emitter–metal nanostructures - Tjahjana, Liliana (2021)
We show the increase of the photoluminescence intensity ratio (PLR) and the emission rate enhancement of perovskite cesium lead bromide (CsPbBr3 ) and formamidinium lead bromide (FAPbBr3 ) nanocrystals (NCs) in the presence of single and double gold layer cavities, which we refer to as Metal-Emitter (ME) and Metal-Emitter-Metal (MEM) nanostructures. Up to 1.9-fold PLRs and up to 5.4-fold emission rate enhancements were obtained for FAPbBr3 NCs confined by double gold layers, which are attributed to plasmonic confinement from the gold layers. The experimentally obtained values are validated by analytical calculations and electromagnetic simulations. Such an effective method of manipulation of the spontaneous emission by simple plasmonic nanostructures can be utilized in sensing and detection applications.